Conversion and storage of solar energy for cooling. Issue 1 (1st September 2021) - Wang, Wenbin; Shi, Yusuf; Zhang, Chenlin; Li, Renyuan; Wu, Mengchun; Zhuo, Sifei; Aleid, Sara; Wang, Peng
Abstract : A passive no electricity and sustainable cooling on-demand (NESCOD) system can convert and store solar energy for cooling. Abstract : Global cooling demands are increasing rapidly as a result of the increasing trends of heatwaves and the increase of living standards. Meeting essential cooling demands by the impoverished is extremely challenging due to their lack of access to electricity. Herein, we report a passive design with dissolution cooling in combination with solar regeneration for the conversion and storage of solar energy for cooling without electricity consumption. As a proof of concept, cooling was achieved by dissolving a NH4 NO3 salt in water and a three dimensional solar regenerator was applied to regenerate the NH4 NO3 salt. The cooling power of such a system could reach up to 191 W m −2 . Importantly, the passive cooling design separates the dissolution cooling and solute regeneration physically and time-wise, allowing for energy storage and utilization even across seasons. This work shines light on the utilization of solar energy for cooling, especially for off-grid communities.